The potential significance of refugia in safeguarding Non-Timber Forest products under Harvesting - Mjoli, Nwabisa (Rhodes University, Faculty of Science, Department of Environmental Science, 2018)
Many rural households living in and adjacent to forests in South Africa harvest a variety of NonTimber Forest Products (NTFPs) such as wild fruits, fibre, fuelwood, seeds, medicine and bush meat for domestic use, sale and maintaining cultural values. To promote the continued availability of these NTFPs it is important that NTFPs are well maintained and that harvest offtake is sustainable, because if it is not, then the important livelihood function that they fulfil will be jeopardized over time. The role of refugia in conserving pockets of threatened species from overharvesting has rarely been considered. Building on Shackleton et al. (2015), six applications of the concept are considered: size refugia, spatial refugia, cultural/spiritual refugia and physical/habitat refugia. I examined the prevalence and type of refugia for NTFPs at three coastal sites in the Eastern Cape province of South Africa. This was done via several community focus group discussions at each site. Here I report on the role of refugia in offering some safeguard to NTFPs by assessing harvested and non-harvested sites of refugia as well as individual plant species by measuring population density, harvest damage and size class profile. Respondents from the focus group discussions perceived a general decline in the abundance of common, widely used species over the past five decades. Decreasing rainfall and distant farming activities was reported consistently by the majority of the respondents. The most common form of refugia was spatial refugia, followed by cultural/spiritual refugia and physical/habitat refugia. Only six species were identified to be in refugia, namely Cyperus congestus, Cyperus textillis, Millettia grandis, Olea europaea subsp. africana, Phoenix reclinata, and Ptaeroxylon obliquum. Population inventories revealed that regeneration and population densities of some NTFP species in the non-refuge site were adversely affected by harvesting. Populations in refuge sites generally had the largest size classes indicating a regeneration potential but likely to impact regeneration over time if pressures are maintained. Therefore, if refuge sites keep larger individuals, NTFP populations can be maintained. Few studies have critically analyzed the concept of refugia in relation to how NTFPs can be safeguarded and the practical implication of the refuge concept needs to be considered in conservation and strategies and population models.
Keywords: Non-timber forest products -- South Africa -- Eastern Cape; Nature conservation -- South Africa -- Eastern Cape; Ecosystem management -- South Africa -- Eastern Cape